The extraterritorial reach of EU competition law revisited: The "effects doctrine" before the ECJ - Peter Behrens (Europa-Kolleg Hamburg, Institute for European Integration, 2016)
The protection of a "system of undistorted competition" within the internal market is one of the core elements of EU law that institutionalizes economic integration. The addressees of the prohibitions regarding restraints of competition such as Articles 101 and 102 TFEU are "undertakings". Hence the question arises whether such undertakings must be located within the EU, whether at least their anticompetitive conduct must be completed within the EU or whether it is sufficient that the effects of restraints of competition are felt on the internal market. These problems have been discussed for many decades, but the ECJ has still not come to a fully satisfactory conclusion. This paper sets out the public international law ramifications, briefly describes the development in the US and analyzes the jurisprudence of the ECJ up to the recent Intel judgment of the General Court which is now, upon appeal, before the ECJ.
Keywords: 320; competition law; antitrust law; extraterritorial application; international jurisdiction; public international law principles; territoriality principle; personality principle; jurisprudence; single economic entity doctrine; implementation doctrine; effects doctrine; conflicts of jurisdiction; positive comity